Active role of teachers in increasing student learning motivation in physical education learning - Thoriq Fajar Ramadhan; Azhar Ramadhana Sonjaya; Ani Kurniawati (Universitas Suryakancana, 2026)
This research is motivated by the importance of the active role of teachers in increasing students' learning motivation in PJOK learning. The purpose of this study is to find out the extent of the active role of teachers in increasing student learning motivation at MTs Al-Musadaddiyah Garut. The method used was a quantitative descriptive approach involving 33 students as respondents, using data collection techniques in the form of questionnaires and interviews. The results showed that the active role of teachers was in the good category with a percentage of 76%, while students' learning motivation reached 78.4% with a good category. These findings show that the more active teachers are in managing learning, the higher the students' motivation to learn. Thus, the purpose of the activity was achieved, namely the positive relationship between the active role of teachers and students' learning motivation in PJOK learning.